2023
DOI: 10.3847/2041-8213/ad0e6b
|View full text |Cite
|
Sign up to set email alerts
|

Early-time Ultraviolet and Optical Hubble Space Telescope Spectroscopy of the Type II Supernova 2022wsp

Sergiy S. Vasylyev,
Christian Vogl,
Yi 轶 Yang 杨
et al.

Abstract: We report early-time ultraviolet (UV) and optical spectroscopy of the young, nearby Type II supernova (SN) 2022wsp obtained by the Hubble Space Telescope (HST)/STIS at about 10 and 20 days after the explosion. The SN 2022wsp UV spectra are compared to those of other well-observed Type II/IIP SNe, including the recently studied Type IIP SN 2021yja. Both SNe exhibit rapid cooling and similar evolution during early phases, indicating a common behavior among SNe II. Radiative-transfer modeling of the spectra of SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These effects are included in their latest analytical model. Line blanketing in the UV is observed in the few earlytime UV spectra of SNe II (Brown et al 2007;Vasylyev et al 2022Vasylyev et al , 2023Bostroem et al 2023a;Zimmerman et al 2024). Recently, Zimmerman et al (2024) confirmed the presence of emission lines from highly ionized species in the UV, as well as photospheric absorption features that appear in the UV while the optical spectrum is still a smooth continuum around T ∼ 15,000 K. 3.…”
Section: Color Evolutionmentioning
confidence: 88%
“…These effects are included in their latest analytical model. Line blanketing in the UV is observed in the few earlytime UV spectra of SNe II (Brown et al 2007;Vasylyev et al 2022Vasylyev et al , 2023Bostroem et al 2023a;Zimmerman et al 2024). Recently, Zimmerman et al (2024) confirmed the presence of emission lines from highly ionized species in the UV, as well as photospheric absorption features that appear in the UV while the optical spectrum is still a smooth continuum around T ∼ 15,000 K. 3.…”
Section: Color Evolutionmentioning
confidence: 88%